Experimental Study on Strengthening Effect Analysis of a Deteriorated Bridge Using External Prestressing Method - Sang-Hyun Kim; Jong-Sup Park; Woo-Tai Jung; Tae-Kyun Kim; Hee-Beom Park (Applied Sciences, 2021)
The external prestressing method was developed to improve the load carrying capacity of concrete bridges damaged by ageing or other external environmental factors. Therefore, it is necessary to examine the performance of the structure before and after strengthening, and verification and confirmation of the actual strengthening effect should be preceded. However, for reasons such as securing deteriorated bridges and the absence of design data, the strengthening effect of an actual bridge is rarely analyzed. Hence, in this study, the strengthening effect was verified by conducting a set of material property tests and four-point loading tests before and after strengthening of an actual bridge, which had been utilized for over 45 years. As a result, it was determined that confirming the strengthening effect before cracking is challenging due to the nature of the external prestressing method, which has an insignificant effect on the stiffness; however, the effect of increasing the crack load of the external prestressing method was experimentally verified. The result of the study is expected to contribute to the determination of the load carrying capacity and required strengthening amount when strengthening existing prestressed concrete girder bridges.